Experiences of participation in everyday activities for people with stroke in Nairobi, Kenya. Issue 5 (4th July 2023) - Kamwesiga, Julius; Bergström, Aileen; Bii, Andrew; von Koch, Lena; Guidetti, Susanne
ABSTRACT: Background: Stroke is currently one of the greatest causes of disability and death in Kenya. Previous research indicates a lack of knowledge regarding how participation in everyday life is experienced after a stroke in Sub-Sahara Africa. Objectives: The aim was to explore and describe experiences of participation in everyday life for people who had had a stroke living in Nairobi, Kenya. Methods: A qualitative study design using semi-structured interviews with nine people who have had a stroke, together with their caregivers. The inclusion criteria were: 1) stroke diagnosis 2) no psychiatric diagnosis, and 3) ability to understand and respond to instructions in English, or local language. All participants were living in the community, members of the Stroke Association of Kenya, and participated voluntarily. The transcribed interviews were analyzed using qualitative content analysis. Results: The participants expressed their experiences of participation in everyday life, along with how resources and barriers affected their participation. Three categories were found: 1) A sense of satisfaction at being involved in everyday life, 2) Challenges in doing everyday activities and social participation, and 3) Dependence as enabling or hindering participation. Conclusions: After stroke, people's experiences of participation in everyday life changed. Performing activities that the person found meaningful added a sense of increased participation and satisfaction. The experience of being dependent in everyday activities and finances appeared to reduce perceived participation. Participation in a group connected to a patient association with like-minded people contributed to a new role, and a sense of belonging.